Legal Protection of Copyright as a Complaint Offense From a Criminal Law Perspective - Br Pardede, Alya Nazwa; Abduh, Rachmad (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
Currently in Indonesia there are many cases of criminal acts against copyright. This number is quite fantastic when you look at the fact that from what is known the number is already quite high, not to mention small cases that do not receive special attention by the government. Of course, if left unchecked, this could cause losses, not only for the creator of the work, but also have an impact on the country's social aspects and even the country's economic aspects. This research uses a normative juridical type of research, what is meant by normative juridical research is legal research. literature because normative legal research is carried out by examining library materials or secondary data only. The legal materials referred to will also be used as interesting literature reviews and books, and web-based resources. The occurrence of copyright crimes can harm the creators and thus legal action must be taken against copyright holders during this process. Criminal law against copyright criminals will be implemented. gradually investigation, investigation, prosecution and investigation in court. The concept of the criminal act of complaint offense (klacht delict), from the meaning of the word klacht or complaint, means a criminal act that can only be prosecuted after a report contains a request for prosecution in relation to a particular person or persons. As a country that has ratified TRIPs (Trade Related Aspects of Intellectual Property Rights), this means that Indonesia has a strong enough legal basis to protect the owners or holders of Intellectual Property Rights (IPR), which include Copyright. Copyright Law Number 28 of 2014 has adapted to the agreement agreed in TRIPs. Based on the description above, it can be concluded that the offense of complaints in copyright crimes is not appropriate for the use of copyright crimes. This is because the substance of ordinary offenses has more relevance to prosecuting copyright crimes. In the description above, the state's responsibility to protect citizens, in this case copyright holders, has been explained. The recommendation regarding this problem is to make or formulate copyright crimes into ordinary offenses. So that law enforcers do not hesitate in carrying out inquiries, inquiries and prosecutions for copyright crimes. So don't wait for complaints from copyright holders. The complaint offense will limit law enforcement